Hubungan Riwayat Kontak Erat dan Kepatuhan Minum Obat Anti Tuberculosis dengan Kejadian Tuberculosis Paru di UPT Puskesmas Medan Sunggal - Ivonne Ruth Vitamaya Oishi Situmeang (Majalah Ilmiah METHODA, 2026)
Tuberculosis (TB) is an infectious disease caused by a complex infection with Mycobacterium tuberculosis. Previous research has shown that a history of close contact and medication adherence are risk factors that can exacerbate and increase the potential for pulmonary TB. The purpose of this study was to determine how a history of close contact and medication adherence influence the incidence of pulmonary TB in adults at the Medan Sunggal Community Health Center (UPT Puskesmas) in 2026. This analytical, observational study used a cross-sectional design, where data relating to the independent or risk variables and the dependent or outcome variables were collected simultaneously. The population in this study consisted of all patients recorded in the medical records at the Medan Sunggal Community Health Center between January 1, 2026, and April 26, 2026. The sampling technique used total sampling, and based on available data, a total sample of 82 individuals was obtained. From the results of this study, there is a relationship between the history of close contact and the incidence of tuberculosis with a p-value < 0.05, and there is a relationship between medication adherence and the incidence of tuberculosis with a p-value < 0.05. The results showed a relationship between a history of close contact and medication adherence with the incidence of pulmonary TB in adults at the Medan Sunggal Community Health Center (UPT Puskesmas).